Update on Treatment of Hypertension After Renal Transplantation - Chatzikyrkou, Christos; Schmieder, Roland; Schiffer, Mario (Current Hypertension Reports, 2021)
Purpose of Review: To incorporate novel findings on pathophysiology and treatment of posttransplant hypertension. Recent Findings: (1) The sodium retaining effects of CNIs are mediated by stimulation of the thiazide-sensitive sodium chloride co-transporter in the distal convoluted tubule and in this regard chlorthalidone was proven to be an effective antihypertensive drug in renal transplantation. (2) Local and not systemic activation of the renin-angiotensin-aldosterone system plays a crucial role in the pathogenesis of posttransplant hypertension. (3) Recent randomized controlled trials failed to prove the presumed superiority of renin-angiotensin blockers in kidney transplantation. (4) Steroid-free and mammalian target of rapamycin-based immunosuppressive drug combinations did not show favorable effects on blood pressure control. (5) In a recent report the risk of non-melanoma skin cancer was higher with thiazide diuretics. But the increased cancer risk in transplant recipients is mainly attributed to comorbidities, such as diabetes and hypertension and of course to the transplantation condition itself or the obligatory application of immunosuppression, and has little to do with the antihypertensive medication Summary: Actual recommendations about BP targets in adult renal transplant recipients are coming from a post hoc analysis of a large randomized trial with another primary endpoint. Unless convincing studies on treatment of hypertension after renal transplantation are available, the ESC/ESH Guidelines 2018 should apply for these patients.
CRIS-Team Scopus Importer:2021-05-21
Keywords: Antihypertensive drugs; Cardiovascular disease; Guidelines; Hypertension; Kidney transplant; Thiazide diuretics